When Shepherds Mine Mountains: The Impact of Artisanal Mining on Agropastoral Systems in Kyrgyzstan. Case Study of Naryn Province - Irène Mestre (Revue de Géographie Alpine)
In 2009, Kyrgyzstan adopted a community-based pasture management model. While agropastoralism is the main subsistence activity for 65% of the population living in rural areas, pastures are also an essential resource for other activities, such as mining. By analysing a rural municipality where agropastoralism and mining co-exist, we explore the impacts of artisanal mining activities on community-based pasture management and territorial resilience. Our key findings show that mining income is capitalised in the form of livestock, and that the mechanisms for animal herding by agropastoralists who are not involved in mining activities and who live on the periphery and have little access to formal decision-making processes are at risk of further marginalisation. Furthermore, the lack of mechanisms for collecting and analysing data on the state of the natural resources necessary for agropastoralism, such as water and pastures, poses a risk to community-based pasture management. Finally, interactions within the system and between the system and external components are a transversal issue for the maintenance of community-based management. Thus, the co-existence of high income–generating activities and traditional activities such as agropastoralism does not limit community-based management and can even be a lever for a dynamic process that helps to support the creation of management rules.